Capacitive deionization of NaCl solutions with ambient pressure dried carbon aerogel microsphere electrodes. Issue 57 (19th July 2017) - Quan, Xueping; Fu, Zhibing; Yuan, Lei; Zhong, Minglong; Mi, Rui; Yang, Xi; Yi, Yong; Wang, Chaoyang
Abstract : We first used carbon aerogel microspheres prepared via emulsion polymerization and ambient drying techniques as electrode material for capacitive deionization. Abstract : Carbon aerogel (CA) microspheres were pyrolyzed from resorcinol–formaldehyde (RF) organic aerogels, which were prepared by emulsion polymerization of resorcinol and formaldehyde using ambient drying technique. Structural and microstructural characteristics of CA microspheres were investigated by scanning electron microscopy (SEM), Raman spectroscopic techniques and nitrogen adsorption. The SEM images show that the resultant CA microspheres are all fine spherical without cracks. Results of Raman spectroscopy indicate that CA microspheres are mainly formed by amorphous carbon structure with a few graphite carbons. The surface area and porosity analysis prove that the CA microspheres have high specific surface area (910 m 2 g −1 ), appropriate pore size distribution (PSD) (3–15 nm) and high ratio of mesoporosity (44%). The results of cyclic voltammetry indicate that the CA microspheres have ideal capacitive behavior, and the maximum specific capacitance values of 83 F g −1 was measured at a scan rate of 10 mV s −1 in 1 M NaCl. These parameters can significantly improve the desalination capacity for the carbon-based electrode materials in capacitive deionization (CDI). The performance of CDI is investigated by different solution concentrations (500–650 mg L −1 ) and applied voltages (0.8–1.4 V). With the optimum initial NaCl concentration of 500 mg L −1 and applied voltage of 1.2 V, the specific salt-adsorption capacity for CA microspheres was found to be 5.62 mg g −1 . The electrosorption and electrodesorption procedures displayed the stability and regeneration of CA microsphere electrodes. This preliminary study demonstrated that the CA microsphere electrodes in CDI process can be considered to be an alternative candidate for desalination.